A PRELEMINARY STUDY OF PAGU PROVERBS STRUCTURE: AN ENDANGERED LANGUAGE IN EASTERN INDONESIA - Dalan Perangin-Angin (Jurnal Masyarakat dan Budaya, 2013)
This article aims (1) to document proverbs in the Pagu language and (2) to analyse their structure, figure of speech, as well as semantic features. The proverbs documentation (in the Pagu language is known as o demo ma daili, lit: ‘language of examining’) is expected to help revitalizing this endangered language. There are 23 'proverbs' collected during a fieldwork in June 2013 to several villages, in which the inhabitants speak Pagu language. This study found that simile and metaphor are the most common features of Pagu proverbs (eleven and six consecutively). Simile describes the similarity between two things, which is overtly marked by the use of soka ‘like’. Meanwhile, metaphor is comparing without comparative words. Keywords: proverbs, simile, metaphor